2020
DOI: 10.1186/s13052-020-0808-6
|View full text |Cite
|
Sign up to set email alerts
|

MKRN3 and KISS1R mutations in precocious and early puberty

Abstract: Background: Pubertal timing is known to be influenced by interactions among various genetic, nutritional, environmental and socioeconomic factors, although the ultimate mechanisms underlying the increase in pulsatile GnRH secretion at puberty have yet to be fully elucidated. The aim of our research was to verify the role of KISSR1 (previously named GPR54) and MKRN3 genes on pubertal timing. Methods: We analyzed the DNA sequence of these genes in 13 girls affected by central precocious puberty (CPP) who showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…All patients were female (age, 5-8 years) recruited between April 2020 and August 2020. The diagnostic criteria used were consistent with the previous study ( 12 ). The inclusion criteria were as follows: Patients diagnosed with ICPP who had been treated with GnRHa with a follow-up >3 months and complete clinical data.…”
Section: Methodssupporting
confidence: 54%
“…All patients were female (age, 5-8 years) recruited between April 2020 and August 2020. The diagnostic criteria used were consistent with the previous study ( 12 ). The inclusion criteria were as follows: Patients diagnosed with ICPP who had been treated with GnRHa with a follow-up >3 months and complete clinical data.…”
Section: Methodssupporting
confidence: 54%
“…One of the most stimulating developments in this field has been the identification of genetic mutations underlying sporadic and familial cases of CPP [ 6 , 7 ]. We recently reported the presence of mutations and polymorphisms of KISS1R and MKRN3 genes, not only in CPP patients but also in subjects with anticipated puberty [ 12 ]. The hypothalamic hamartoma represents the most common organic cause in both sexes, usually manifesting before 4 years of age [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a 2019 review of the contribution of these genes to both HH and CPP, Ke et al extensively reviewed previously reported cases and demonstrated the biochemical relevance of the location of the mutations on the functionality of the protein, and noted that some mutations of KISS1/KISS1R can be associated in both HH and CPP [47]. Since then, there have been a handful of studies from various countries that show polymorphisms of KISS1/KISSR1 in their cohorts [60][61][62][63][64].…”
Section: Kisspeptin (Kiss1) and Kisspeptin Receptor (Kiss1r Or Gpr54)mentioning
confidence: 99%